MODEL RENCANA BISNIS PRODUKSI GELATIN DARI LIMBAH PENGOLAHAN IKAN - Johar Arief (Kurs : Jurnal Akuntansi, Kewirausahaan dan Bisnis, 2016)
Gelatin is protein substance, produced by partial hydrolysis of collagen extracted from the bones, skin or any other organs of animals. Nowadays, the needs of gelatin products are increasing in many fields, such as pharmaceutical, food industry, cosmetics industry, and many others. In fact, almost 100% Indonesia’s gelatin demand is imported. Indonesia has abundant resources to produce gelatin. One of the sources for producing gelatin is supplied by the fishery industry. The waste or by-products of the fish (such as skin and bones) originated from fish processing companies can be used as raw material to make fish gelatin. This feasibility study of producing fish gelatin in industrial scale carries out an overall cost leadership strategy, emphasizing the aggressive marketing strategy and high quality product control in order to achieve a high and effective market response. Applying this strategy, it is expected to attain an NPV of IDR 25.2 billion, with a 22% MIRR, which is significantly above the 18% Weighted Average Cost of Capital, and has a payback period less than 9 years. Gelatin merupakan substansi protein yang dihasilkan melalui hidrolisa kolagen yang diekstrak dari tulang, kulit, atau organ lainnya dari mamalia. Gelatin dibutuhkan oleh industri utamanya sebagai bahan pengikat dan pengemulsi. Dewasa ini kebutuhan gelatin oleh berbagai industri semakin meningkat, seperti industri makanan, farmasi, dan kosmetik. Sedangkan hampir 100% kebutuhan gelatin dalam negeri dipenuhi melalui impor. Indonesia sebenarnya memiliki bahan baku yang melimpah untuk memproduksi gelatin. Bahan baku tersebut berasal dari industri pengolahan ikan. Limbah industri pengolahan ikan, yakni berupa kulit dan tulang ikan, bisa digunakan sebagai bahan baku untuk membuat gelatin ikan. Studi kelayakan bisnis untuk memproduksi gelatin dalam skala industri ini mengusung strategi overall cost leadership, strategi pemasaran yang agresif, dan pengendalian kualitas produk yang ketat untuk mendapatkan respons pasar yang baik. Melalui strategi ini diharapkan dapat tercapai NPV sebesar 25,2 miliar rupiah, dengan MIRR 22%, dan payback period kurang dari sembilan tahun.